Attention for Distraction: Modernity, Modernism and Perception - van Alphen, Ernst (Text Matters: A Journal of Literature, Theory and Culture, 2017)
Particularly in the latter half of the nineteenth century sensorial experiences changed at breakneck speed. Social and technological developments of modernity like the industrial revolution, rapid urban expansion, the advance of capitalism and the invention of new technologies transformed the field of the senses. Instead of attentiveness, distraction became prevalent. It is not only Baudelaire who addressed these transformations in his poems, but they can also be recognized in the works of novelist Gustave Flaubert and painter Edward Munch. By means of the work of William James, Walter Benjamin, Siegfried Kracauer and Georg Simmel, the repercussions of this crisis of the senses for subjectivity will be discussed.